Agonist antibodies to TNFR molecules that costimulate T and NK cells - Melero, Ignacio (Clin Cancer Res, 2013)
Therapy of cancer can be achieved by artificially stimulating anti-tumor T and NK lymphocytes with agonist monoclonal antibodies. T and NK cells express several members of the Tumor Necrosis Factor-receptor (TNFR) family specialized in delivering a costimulatory signal on their surface. Engagement of these receptors is typically associated with proliferation, elevated effector functions, resistance to apoptosis, and differentiation into memory cells. These receptors lack any intrinsic enzymatic activity and their signal transduction relies on associations with TRAF adaptor proteins. Stimulation of CD137 (4-1BB), CD134 (OX40), and GITR (CD357) promotes impressive tumor-rejecting immunity in a variety of murine tumor models. The mechanisms of action depend on a complex interplay of cytolytic T lymphocytes, helper T cells, regulatory T cells, dendritic cells, and vascular endothelium in tumors. Agonist monoclonal antibodies (mAbs) specific for CD137 have shown signs of objective clinical activity in metastatic melanoma patients while anti-OX40 and anti-GITR mAbs have entered clinical trials. Preclinical evidence suggests that engaging TNFR members would be particularly active with conventional cancer therapies and additional immunotherapeutic approaches. Indeed, T cell responses elicited to tumor antigens by means of immunogenic tumor cell death are amplified by these immunostimulatory agonist mAbs. Furthermore, anti-CD137 mAbs have been shown to enhance NK-mediated cytotoxicity elicited by rituximab and trastuzumab. Combinations with other immunomodulatory mAb that block T cell checkpoint blockade receptors such as CTLA-4 and PD-1 are also promising.